The Size Illusion and Lightness Contrast Effect in Delboeuf-like Displays: Possible Evidence of Percept-Percept Coupling. (July 2014) - Daneyko, Olga; Zavagno, Daniele; Stucchi, Natale
We conducted two experiments to test the relationship between Delboeuf's size-contrast illusion and a concomitant lightness contrast effect that can be observed when achromatic disks are employed as targets. In experiment 1 participants were asked to adjust the diameter of a target (D1) surrounded by a small circular size-inducer (C1) to match in size a comparison target (D2) surrounded by a circular size-inducer (C2) either equal or greater in diameter than C1. Experiment 2 was similar to experiment 1, except that D1 and D2 were physically equal in size, and participants were asked to adjust the luminance of D1 to match D2 in lightness. Results confirm an effect of the difference in diameter between C1 and C2 on the magnitude of the size illusion but not on the magnitude of the lightness effect, the emergence of which is linked to the appearance of the size illusion. Results support a percept-percept coupling relationship.